2002
DOI: 10.1080/14733140212331384958
|View full text |Cite
|
Sign up to set email alerts
|

Experiential congruence: Qualitative analysis of client and counsellor narrative accounts of significant events in time‐limited person‐centred therapy

Abstract: The concept of congruence represents a core theoretical construct in the development of client‐centred therapy, and remains fundamental to the practice of experiential approaches to psychotherapy. This study explores the ways in which congruence is experienced during significant moments of therapy. Client and counsellor accounts of moments of congruence/incongruence were collected from six cases of person‐centred counselling, and were analysed using a method of narrative analysis. It was found that participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Grafanaki and McLeod (2002) found that congruence is not a ''unitary phenomenon.'' Hence, there is value in conceptualizing congruence as a multifaceted construct.…”
Section: Conceptualization Of Congruence In Satir's Systemic Growth Mmentioning
confidence: 97%
See 1 more Smart Citation
“…Grafanaki and McLeod (2002) found that congruence is not a ''unitary phenomenon.'' Hence, there is value in conceptualizing congruence as a multifaceted construct.…”
Section: Conceptualization Of Congruence In Satir's Systemic Growth Mmentioning
confidence: 97%
“…Moreover, research participants tended to be predominantly from the West. To test the crosscultural validity of congruence, Grafanaki and McLeod (2002) and Lee (2002b) recommended that more research be conducted on congruence with participants of different cultural backgrounds. Given the vital role of congruence in therapy, this study, using phenomenological analysis, seeks to explore (a) the Singaporean Chinese therapists' lived experience of congruence in their personal or inner lives; (b) how this congruence is used in psychotherapy; and (c) how therapists enhance their level of congruence.…”
Section: The Present Studymentioning
confidence: 99%
“…As Grafanaki and McLeod (2002) point out this type of honest relationship is fundamental to all therapies. Its multi-dimensional nature has been noted by Lietaer (1993) who identifies the two aspects of genuineness and transparency and Tudor and Worrall (1994) who identify four elements, namely: self-awareness; self-awareness in action; communication; and appropriateness.…”
Section: Congruencementioning
confidence: 97%
“…It highlighted the importance of achieving personal insights and new understandings about the self/issue, as instrumental in monitoring the client's progress. In the literature, good or significant moments of therapy vividly captured the client's ability to experience or express new ways of being or behaving, and acknowledge self-growth and personal insight (Cummings, Slemon, & Hallberg, 1993;Elliott, 1985;Grafanaki, 1997;Grafanaki & McLeod, 2002;Llewelyn, et al, 1988;Mahrer & Nadler, 1986;Martin & Stelmaczonek, 1988).…”
Section: Relevance For Counseling and Psychotherapymentioning
confidence: 98%
“…According to the counseling literature, intense focus and concentration on a meaningful task/topic captured or led to problem clarification, problem solving or insight (Elliott, 1985;Elliott, James, Reimschuessel, et al, 1985;Grafanaki & McLeod, 2002;Llewelyn, Elliott, Shapiro, et al, 1988). Active engagement of the counselor and the client with meaningful, yet challenging (not easy) tasks was important during highly facilitative, helpful moments of therapy that promoted positive therapeutic outcomes (Grafanaki, 1997;Grafanaki & McLeod, 2002). We anticipated that flow moments of therapy would be marked by intense focus and active engagement with meaningful material that helped the client meet goals and overcome challenges.…”
Section: Relevance For Counseling and Psychotherapymentioning
confidence: 99%